EFEKTIVITAS PROGRAM USAHA EKONOMI PRODUKTIF KELOMPOK USAHA BERSAMA MELALUI KELOMPOK USAHA BERSAMA LESTARI BUDAYA SEBAGAI UPAYA PEMBERDAYAAN MASYARAKAT - Rizki Yuliyanto; Hanantyo Sri Nugroho (Halu Oleo University, 2025)
This study uses the theory of program effectiveness with indicators namely program socialization, program target accuracy, program monitoring, and goal achievement. The method used in this research is descriptive qualitative. The results of this study indicate the effectiveness of the joint business group productive business program through Kube Lestari Budaya as an effort to empower the community, in general, has been running well and effectively. This is determined by the indicator of the accuracy of program targets. The targets of the program are met, namely the poor who are registered in DTKS. To ensure that the proposed recipients are by the provisions, the Yogyakarta Special Region Social Service rechecks the data in the Integrated Social Welfare Data System using the NIK (Population Identification Number) that has been included in the proposal. The difference between the pre- and post-programs implemented on both kube provides empowerment that contributes to building motivation to increase production according to the business being run.